2021
DOI: 10.3390/polym13234159
|View full text |Cite
|
Sign up to set email alerts
|

Review on Local Buckling of Hollow Box FRP Profiles in Civil Structural Applications

Abstract: Hollow box pultruded fibre-reinforced polymers (PFRP) profiles are increasingly used as structural elements in many structural applications due to their cost-effective manufacturing process, excellent mechanical properties-to-weight ratios, and superior corrosion resistance. Despite the extensive usage of PFRP profiles, there is still a lack of knowledge in the design for manufacturing against local buckling on the structural level. In this review, the local buckling of open-section (I, C, Z, L, T shapes) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 193 publications
(360 reference statements)
1
9
0
Order By: Relevance
“…All together, these facts seem to indicate that the adhesive installation of the flange connection did not work for the described experimental campaign. In addition, adhesive connections were always associated with fragile debonding failure types (see Table 8 and Figure 3 ), in accordance with existing literature (see [ 25 , 26 ]), whereas bolted connections reached the local failure of the GFRP profile at the web-flange edge as reported by other researchers (see [ 8 , 14 , 15 ]) who studied this phenomena concluding that the roving-rich area in the web-flange junction was the base cause of this response.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All together, these facts seem to indicate that the adhesive installation of the flange connection did not work for the described experimental campaign. In addition, adhesive connections were always associated with fragile debonding failure types (see Table 8 and Figure 3 ), in accordance with existing literature (see [ 25 , 26 ]), whereas bolted connections reached the local failure of the GFRP profile at the web-flange edge as reported by other researchers (see [ 8 , 14 , 15 ]) who studied this phenomena concluding that the roving-rich area in the web-flange junction was the base cause of this response.…”
Section: Discussionsupporting
confidence: 90%
“…Among FRP production technologies, pultrusion [ 7 ] is a consecutive process aimed to produce FRP longitudinal elements with constant cross-sections, by means of using continuous roving soaked with resin ad heated to cure them. Regarding the type of pultruded FRP elements, Alhawamdeh et al [ 8 ] reported the I-shape profiles were the most used ones. Pultruded FRPs have several advantages apart from the general ones directly associated with FRP materials (including corrosion resistance, high strength to weight ratio and durability).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pultrusion is claimed to be the most efficient process for the production of thermoplastic FRP composites with constant cross sections [ 9 ]. Composite profiles of various cross sections (flat laminates, hollow box, I-, U-, C-, L-, and T-shape profiles) are widely used in various sectors of industry—transportation [ 10 ], aerospace [ 11 , 12 ], marine construction [ 13 ], civil engineering, and architecture [ 14 , 15 , 16 , 17 ]. Moreover, due to their high strength-to-weight ratio and excellent corrosion resistance, FRP composite bars have gained engineers’ attention as a possible substitute for steel bars used in reinforced concrete structures [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced thermoset polymer composites are implemented in a variety of industries, such as in civil [ 1 , 2 ] and energy [ 3 , 4 , 5 ] and in recreational and naval marine applications [ 6 , 7 , 8 , 9 , 10 ] as well as in performance automobiles [ 11 , 12 ] and in aerospace applications [ 13 , 14 , 15 ]. The adoption of thermoset materials has increased in recent years due to the tailorability of part properties and wide variety of manufacturing techniques and achievable geometries.…”
Section: Introductionmentioning
confidence: 99%